1980
DOI: 10.1017/s019594170005308x
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Klebsiella Infection in a Neonatal Unit: Identification of Risk Factors for Gastrointestinal Colonization

Abstract: Sequential outbreaks of infection due to gentamicin-resistant Klebsiella pneumoniae (GRKP) types 30 and 19 occurred in the neonatal intensive care unit (NICU) at the Medical College of Virginia in 1977 and 1978. The extensive epidemiologic investigation carried out included a case-control study, careful review of aseptic technique, and cultures from nursery staff and environment. The gastrointestinal (GI) tracts of the patients were the reservoirs for GRKP, and the epidemic strain was transmitted by hands of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 14 publications
(8 reference statements)
2
12
0
Order By: Relevance
“…infections in general, [12][13][14][15] we found the gastrointestinal tract to be a common and important site of colonization. Morgan et al 5 found only two of 12 infected infants did not have rectal colonization at the time of sepsis; all our infants with ESBL Klebsiella sp.…”
Section: Discussionmentioning
confidence: 73%
“…infections in general, [12][13][14][15] we found the gastrointestinal tract to be a common and important site of colonization. Morgan et al 5 found only two of 12 infected infants did not have rectal colonization at the time of sepsis; all our infants with ESBL Klebsiella sp.…”
Section: Discussionmentioning
confidence: 73%
“…Gram-positive cocci, particularly streptococci and Staphylococcus aureus, were the most common cause of hospital-acquired infection in the first half of the century, followed by the emergence of gram-negative bacilli, such as K. pneumoniae and Enterobacteriaceae, in the 1970s [17][18][19]. With the development of antimicrobial agents effective against gram-negative pathogens, gram-positive organisms became the most common cause of infection with the problematic emergence of methicillin-resistant S. aureus [20] and vancomycin-resistant enterococci [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cross‐transmission via HCWs’ hands seems to be important in the nosocomial spread of K. pneumoniae strains . Indeed there is extensive evidence for transmission via the hands of HCWs from colonized patients or environmental reservoirs to new patients, in both epidemic and endemic situations . However, in a recent study, an outbreak caused by contaminated food was described, indicating that transmission may also occur via the food chain .…”
Section: Mechanisms Of Transmissionmentioning
confidence: 99%